2020
DOI: 10.1016/j.contraception.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of CenteringPregnancy group prenatal care on postpartum visit attendance and contraception use

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(39 reference statements)
0
12
1
Order By: Relevance
“…Our primary analysis of between-group differences in outcomes of interest included all participants who completed the postpartum survey regardless of the number (dose) of prenatal care visits attended (ie, group prenatal care visits for participants in the GMPC group and in-person or virtual individual visits for those in the IMPC group). We conducted 3 secondary analyses stratified on varying levels of prenatal care use (dose-stratified analyses); we compared outcomes of GMPC vs IMPC participants who completed at least 1 prenatal care visit (DS1), 5 prenatal care visits (DS5), and 70% of prenatal care visits (DS70%) The 5-visit threshold was based on previous research defining this cutoff as a marker of adequate exposure to in-person group prenatal care . The 70% threshold was conducted to address variation in the number of virtual GMPC group sessions offered by KPNC clinics, which ranged from 7 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary analysis of between-group differences in outcomes of interest included all participants who completed the postpartum survey regardless of the number (dose) of prenatal care visits attended (ie, group prenatal care visits for participants in the GMPC group and in-person or virtual individual visits for those in the IMPC group). We conducted 3 secondary analyses stratified on varying levels of prenatal care use (dose-stratified analyses); we compared outcomes of GMPC vs IMPC participants who completed at least 1 prenatal care visit (DS1), 5 prenatal care visits (DS5), and 70% of prenatal care visits (DS70%) The 5-visit threshold was based on previous research defining this cutoff as a marker of adequate exposure to in-person group prenatal care . The 70% threshold was conducted to address variation in the number of virtual GMPC group sessions offered by KPNC clinics, which ranged from 7 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…All practices offer both CenteringPregnancy group prenatal care and individual prenatal care for patients who chose not to participate in group prenatal care or who are not eligible due to medical comorbidities, pregnancy complications, or late entry to prenatal care. Twenty-one of the 24 practices had data available for this study; previous research found that SCCPEP’s group prenatal care was associated with decreased rates of preterm birth and low birth weight births and increased rates of postpartum visit attendance (Crockett et al, 2019; Heberlein et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Women participating in the CenteringPregnancy model demonstrate increased participation in preventive health services during and after pregnancy, suggesting that the group model may increase health literacy or patient engagement (DeCesare et al, 2017; Grady & Bloom, 2004; Hale et al, 2014; Heberlein et al, 2020; Kennedy et al, 2009; Picklesimer et al, 2012; Roussos-Ross et al, 2020; Schellinger et al, 2017). Research investigating associations between group prenatal care participation and ER utilization is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to enhance psychosocial health have been shown to reduce anxiety, empower individuals, and result in better glycemic control among individuals with GD, but they are not aimed to reduce GD risk. Group prenatal care (GPNC) is an innovative model of medical care to improve clinical outcomes and health behaviors and to reduce racial disparities . CenteringPregnancy (Centering Healthcare Institute, Boston, Massachusetts) is the most widely implemented GPNC model and includes a curriculum specifically targeting elements of healthy lifestyle and behaviors (eg, nutrition, exercise, goal setting, and self-care) and psychosocial improvement (eg, stress management, empowerment, and peer and family support) .…”
Section: Introductionmentioning
confidence: 99%